(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Food selectivity is characterized by food selection and restriction, which can result in malnutrition and health impacts. The objective of this study was to verify the effectiveness of the Fading and Simultaneous Presentation procedures for inserting a new food, with a 12-year-old male participant, with a history of food selectivity and refusal behaviors, mainly anticipatory cough and vomiting. Baseline, intervention, intermediate and final probes and generalization assessment sessions were held. The combined procedures were effective for the ingestion of the new food, with progressive stages of texture presentation, combined with Simultaneous Presentation of the non-preferred food with the preferred one. When presented alone in the probe sessions, the non-preferred food was not ingested. Follow-up sessions were held at home, monitored by the mother, with success in ingesting the foods presented simultaneously and included in the usual menu.